Nitrogen dynamics in low-arctic streams are linked to terrestrial vegetation cover - Jakob Breinholt Kjær; Katrine Raundrup; Kirsty Langley; Tenna Riis (Arctic Science)
The Arctic is experiencing rapid climatic changes, leading to landscape shifts, including increased vegetation cover (greening) and altered nutrient dynamics. This study examines the relationship between catchment vegetation cover, measured by the normalized difference vegetation index (NDVI), and dissolved inorganic nitrogen and dissolved organic nitrogen concentrations in streams in Kobbefjord region in low-Arctic West Greenland. Water samples from streams were collected weekly across three catchments with varying vegetation cover during summer 2023. Our results showed a significant negative relationship between catchment NDVI and stream nitrate (NO3 −) concentrations. The results support what has previously been found in high-Arctic streams in Northeast Greenland and thus expand the generality of this pattern in a broader Arctic context. The results suggest that greening in low-Arctic areas could reduce the annual N export from terrestrial to aquatic systems. However, the variation in export during the summer season is driven by discharge. Thus, the future projected greening and increased summer precipitation will most likely alter nutrient availability and primary production in the coastal ecosystems of the Arctic Ocean. Such changes may have significant ecological consequences not only for the coastal ecosystems but also for the Arctic communities that rely on these ecosystems.